2013
DOI: 10.3390/molecules181113369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, X-ray Structure and Biological Activities of C-5-Bromo-2-hydroxyphenylcalix[4]-2-methyl resorcinarene

Abstract: properties and antioxidant activity were also investigated. It was strongly antiviral against HSV-1 and weakly antibacterial against Gram-positive bacteria. Cytotoxicity testing on Vero cells showed that it is non-toxic, with a CC 50 of more than 0.4 mg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Chloramphenicol was 100-200 fold more active than the tested compound in microtiter plate. Similar results were obtained previously in our group [40] as well as by Abosadiya and his co-researcher [17]. It was found that Gram-positive bacteria were more susceptible than Gram-negative test strains at concentrations comparable to the used ones in this work or even higher.…”
Section: In Vitro Antimicrobial Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…Chloramphenicol was 100-200 fold more active than the tested compound in microtiter plate. Similar results were obtained previously in our group [40] as well as by Abosadiya and his co-researcher [17]. It was found that Gram-positive bacteria were more susceptible than Gram-negative test strains at concentrations comparable to the used ones in this work or even higher.…”
Section: In Vitro Antimicrobial Activitysupporting
confidence: 92%
“…They present well-defined conformational properties and cavities with molecular dimensions that enable them to encapsulate guest drugs [14]. Though most of the calixarene components have been reported for their efficacy against few microorganism species [15][16][17], some calixarenes have shown interesting activities against cancerous cells [14,18].…”
Section: Ternary Inclusion System Of Chair Conformation 207mentioning
confidence: 99%
“…The compound C‐ 4‐acetamidophenylcalix[4]‐2‐methyl resorcinarene was synthesized by using one‐pot condensation reaction, similar procedure was used for the previously reported C ‐5‐bromo‐2‐hydroxyphenylcalix[4]‐2‐methylresorcinarene . The condensation reaction of 2‐methylresorcinol with 4‐acetamidobenzaldehyde in the presence of concentrated HCl in EtOH at 80 °C afforded 83% yield of the methylresorcin[4]arene product (I) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the formation of simple dimeric hydrogen bonded capsules of C ‐Alkylcalix[4]resorcinarenes from tert‐butanol and other alcoholic solvents have been reported . Recently, some derivatives of calix[4]resorcinarene have shown high biological activities as antiviral against HSV‐1 and good antioxidant activity at noncytotoxic concentrations . Over the past three decades, many calix[4]resorcinarenes containing aliphatic linkage groups have been reported and some of them have been applied to chiral recognition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inactivity of the title compound could be attributed to its hydrophobic and nonpolar properties. A bulky calixerane derivatives compound has been reported to give a significant antibacterial activity [27]. It shows the presence of the hydrophilic groups such as hydroxyl plays an important role although the molecule is large.…”
Section: Calculated Values Are In the Bracketmentioning
confidence: 99%